Prevalence of virulence determinants and antibiotic resistance patterns of Enterococcus faecalis strains in patients with community-acquired urinary tract infections in Iran. Issue 6 (2nd November 2018) - Karimi, Abdullah; Ghalavand, Zohreh; Fallah, Fatemeh; Eslami, Parisa; Parvin, Mahmoud; Alebouyeh, Masoud; Rashidan, Marjan
ABSTRACT: The aim of this study was to characterize virulence factors and antibiotic resistance patterns in E. faecalis strains obtained from community-acquired urinary tract infections. A total of 70 E. faecalis isolates from Labbafinejad Hospital in Tehran were collected. Antibiotic resistance and virulence determinants were examined by phenotypic and molecular methods. Among 70 E. faecalis isolates, efba (97.1%), ace (95.7%), and gelE (94.3%) were the most prevalent virulence genes. The most common antibiotic resistance pattern was tetracycline (88.6%) and minocycline (87.1%). Multi-drug resistant phenotype was detected among 10% of them. Our results showed capability of E. faecalis strains for infection of the urinary tract in community. Involvement of virulence determinants in the pathogenesis of community acquired E. faecalis strains was proposed due to their high prevalence rates. Food producing animals were proposed as their environmental reservoirs, due to dominance of tetracycline resistance phenotype among them.